A Rare Ocular Anomaly of Congenital Bilateral Aphakia in a Goat Kid - A Case Report - Kumaran, M Senthil; Senthamizhan, S; Vishnugurubaran, D; Vijayakaran, K; Arunmozhi, N; Vijayarajan, A (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Ocular defects in food-producing livestock have a  significant impact on the economy of the rearing  community. Every year there is an increase in the number of  food-producing animals and reports of congenital anomalies  become evident in the total number of animals affected  per year (Williams, 2010). Reports on ocular anomalies in  ruminants that too in the eyes of sheep and goats are very  limited (Sangamwar et al., 1997). Aphakia means absence of  lens. Congenital aphakia is an exceptionally rare anomaly  that is reported only in very few livestock. This anomaly is  either due to the failed induction of lens placode or due  to the resorption or expulsion of the lens in utero after  normal development (Gelatt and Plummer, 2022). Aphakia  is commonly associated with anterior segment dysgenesis.  The diagnosis can be done with slit lamp biomicroscopy,  retinoscopy and ultrasonography. Enucleation is one of the  choices of treatment in livestock (Sato et al., 2017).
Keywords: macroscopically; aphakia